''Ivo Andrić'' o Žutoj kući ili jedan pamflet o Ministarstvu inostranih poslova Kraljevine Jugoslavije - Ratomir Milikić (Istorija 20. Veka, 2018)
Handing out pamphlets denouncing the work of state institutions in the interwar period for the purposes of the new communist authorities was not at all uncommon in the period right after the liberation of Belgrade, in October 1944. The document described here is one such. What makes it special is that it was attached to the personal file of a high-ranking interwar diplomat and novelist Ivo Andrić. A subsequent Nobel Prize winner in literature, he was known to the expert community for notable passive resistance to the occupier, with likely contacts with the Yugoslav Army in the Fatherland. A scholarly critique has been used in the paper to clarify that Andrić had not authored the pamphlet. The paper also sheds some light on the anonymous author, as well as the time and purpose of the release of his writing. The pamphlet was clearly designed to defame the Ministry of Foreign Affairs of the Kingdom of Yugoslavia (occasionally dubbed the “Yellow House”), levelling serious accusations against the descendants of elite families working at the Ministry, and the key figures in the institution. In the best gutter-press tradition, the document criticized indolence and inefficiency, crimes and espionage, inadequacy and corruption, without giving an opportunity to the targets of criticism to respond in any way. It is noteworthy that the labelled were (almost) exclusively Serbs. Even though most of the ministry staff were Serbian nationals, the criticism carefully bypassed all other ethnicities, along with the people that might have been close to the new authorities. The bias and clear intention to slander the old regime notwithstanding, the document does have historical significance insofar as it provides insight into a rather hazy period, in which the new Serbian authorities took over, and into the general working environment the Kingdom’s diplomatic and consular representatives had coped with in the years between the two wars.